Business in practice - innovation management - Mari, Marin Paul Marius (2022)
In group of six, we have been put in charge of managing an automotive firm during its transition to a more ecological and sustainable model. We developed our team and strategies for the different department in order to generate the most value added and renew the whole portfolio. This paper is a summary of the three weeks of simulation we went through and the different strategy and methods we used to make our firm successful.